Modernisasi dan Reformasi Pesantren: Upaya Preventif Menjaga Citra Pesantren di Indonesia - Hamdi Hamdi; Noorazmah Hidayati; Abid Nurhuda; Ali Anhar Syi’bul Huda; Yulita Putri (CV. Eureka Artha Nusantara, 2026)
Islamic boarding schools (pesantren) in Indonesia face the paradox of modernization: on the one hand, they must adapt to the demands of the times, while on the other, they must preserve their traditional identity. The widespread negative reporting and rigid religious practices have eroded public trust and the image of pesantren. This study analyzes the modernization and reform of pesantren as a preventive strategy to maintain their image and relevance. Using a qualitative approach and systematic literature review, data were collected and analyzed through Miles and Huberman’s techniques (reduction, display, verification). The findings reveal three patterns of modernization: first, digitalization of educational content and management; second, integration of the national curriculum with local wisdom of pesantren; and third, transformation of socio-economic roles through social entrepreneurship. The analysis indicates that pesantren modernization requires a